Lipid extract derived from newly isolated Rhodotorula toruloides LAB-07 for cosmetic applications - Junyeob Kim; Eun-Jung Lee; Kyung-Eun Lee; Youn-Hwa Nho; Jeoungjin Ryu; Su Young Kim; Jeong Kyun Yoo; Seunghyun Kang; Sang Woo Seo (Computational and Structural Biotechnology Journal, 2023)
Rhodotorula toruloides is a non-conventional yeast with a natural carotenoid pathway. In particular, R. toruloides is an oleaginous yeast that can accumulate lipids in high content, thereby gaining interest as a promising industrial host. In this study, we isolated and taxonomically identified a new R. toruloides LAB-07 strain. De novo genome assembly using PacBio and Illumina hybrid platforms yielded 27 contigs with a 20.78 Mb genome size. Subsequent genome annotation analysis based on RNA-seq predicted 5296 protein-coding genes, including the fatty acid production pathway. We compared lipid production under different media; it was highest in the yeast extract salt medium with glycerol as a carbon source. Polyunsaturated α-linolenic acid was detected among the fatty acids, and docking phosphatidylcholine as a substrate to modeled Fad2, which annotated as Δ12-fatty acid desaturase showed bifunctional Δ12, 15-desaturation is structurally possible in that the distances between the diiron center and the carbon-carbon bond in which desaturation occurs were similar to those of structurally identified mouse stearoyl-CoA desaturase. Finally, the applicability of the extracted total lipid fraction of R. toruloides was investigated, demonstrating an increase in filaggrin expression and suppression of heat-induced MMP-1 expression when applied to keratinocytes, along with the additional antioxidant activity. This work presents a new R. toruloides LAB-07 strain with genomic and lipidomic data, which would help understand the physiology of R. toruloides. Also, the various skin-related effect of R. toruloides lipid extract indicates its potential usage as a promising cosmetic ingredient.